Reliability of ductility requirements in concrete design codes. (September 2016) - Baji, H.; Ronagh, H.R.; Melchers, R.E.
Highlights: Current state of the art does not adequately address the probabilistic nature of ductility as it does for the strength. Ductility is sensitive to a wider range of random variables compared to strength. Uncertainty in the ductility of RC beam sections is far higher than that of strength. There is larger disparity among codes for the reliability of ductility compared to those for strength. Abstract: Ductility is an important limit state for the design of reinforced concrete beams. Its implementation varies considerably between design codes. This is investigated using reliability-based assessment with ductility defined by strain ratio. The modelling uncertainty for the ductility limit state typically is much greater than that for structural strength limit state. This is reflected in the corresponding reliability indices of limit state defined for ductility. Some of these could be considered unacceptably low.